2012
DOI: 10.1111/j.1469-7580.2012.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and development of the vertebrate neck

Abstract: Muscles of the vertebrate neck include the cucullaris and hypobranchials. Although a functional neck first evolved in the lobe-finned fishes (Sarcopterygii) with the separation of the pectoral ⁄ shoulder girdle from the skull, the neck muscles themselves have a much earlier origin among the vertebrates. For example, lampreys possess hypobranchial muscles, and may also possess the cucullaris. Recent research in chick has established that these two muscles groups have different origins, the hypobranchial muscles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 71 publications
(136 reference statements)
0
78
0
2
Order By: Relevance
“…A major evolutionary issue regarding the pectoral region of tetrapods that attracts much attention concerns the muscle protractor pectoralis, mainly due to its implications for the origin and evolution of the neck in vertebrates (Diogo and Abdala, ; Ericsson et al, ). Edgeworth () defended that the protractor pectoralis is a head muscle derived in both ontogeny and phylogeny from the levatores arcuum branchialum group that has markedly extended posteriorly during tetrapod evolution to cover a substantial part of the neck, pectoral girdle, and back regions, as seen for instance in adult humans (where the muscle gave rise to the trapezius and sternocleidomastoideus).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major evolutionary issue regarding the pectoral region of tetrapods that attracts much attention concerns the muscle protractor pectoralis, mainly due to its implications for the origin and evolution of the neck in vertebrates (Diogo and Abdala, ; Ericsson et al, ). Edgeworth () defended that the protractor pectoralis is a head muscle derived in both ontogeny and phylogeny from the levatores arcuum branchialum group that has markedly extended posteriorly during tetrapod evolution to cover a substantial part of the neck, pectoral girdle, and back regions, as seen for instance in adult humans (where the muscle gave rise to the trapezius and sternocleidomastoideus).…”
Section: Discussionmentioning
confidence: 99%
“…That is, according to these studies the trapezius is a rather peculiar muscle that is seemingly directly associated with three different types of connective tissue: derived from branchial arch crest cells, somite‐derived, and lateral plate‐derived (forelimb). Therefore, authors have questioned whether the protractor pectoralis and its amniote derivatives trapezius and sternocleidomastoideus are primarily derived from the paraxial mesoderm, as suggested by Edgeworth (), and only later became ontogenetically associated with the cranialmost somites and even with lateral plate‐derived connective tissue of the forelimb, or are instead primarily derived from somites (Ericsson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of cranial neural crest cells to the connective tissue of cranial muscles was investigated also in amphibians (reviewed in Schmidt et al 2013 andEricsson et al 2013). Using DiI labelling, green fluorescent protein (GFP) mRNA injection and transplantation of neural folds, Olsson's group showed that cranial neural crest cells form the connective tissue but not the myofibers in the branchiomeric muscles in Bombina orientali (Olsson et al 2001) and in Ambystoma mexicanum ).…”
Section: Cranial Neural Crest Cells Form the Connective Tissue Of Thementioning
confidence: 99%
“…A.mexicanum and T.roseae both share a specific organization of neck muscles, which goes around their gills and allows them to move the head (Ericsson R et al, 2012). A.mexicanum and T.roseae also both share appendicular skeleton which connect to their neck muscles (Ericsson R et al, 2012). A.mexicanum and T.roseae have both been shown to be closely related as they have been put on the same clade on morphological 2016. phylogenies (Shubin H et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A.mexicanum and T.roseae have been shown to share many synapomorphies (Ericsson R et al, 2012). A.mexicanum and T.roseae both share a specific organization of neck muscles, which goes around their gills and allows them to move the head (Ericsson R et al, 2012). A.mexicanum and T.roseae also both share appendicular skeleton which connect to their neck muscles (Ericsson R et al, 2012).…”
Section: Discussionmentioning
confidence: 99%